Measuring technological bias - Stevenson, Rodney (American Economic Review, 1980)
In this paper, a model based on the translog cost function and designed to test for technological advancement, factor-input and scale biases arising from technological advancement, and induced technological bias is described. The model is estimated with data from the electrical utility generation industry. While the empirical results for that industry demonstrate the existence of technological advancement and technological bias, both with regard to factor inputs and scale economies, the results failed to demonstrate the existence of induced technological bias. The results of this study indicate an average annual rate of technological advancement of approximately 1.5 percent while the average observed rate is 1.7 percent.